PENERAPAN GERAKAN LITERASI SEKOLAH DI SEKOLAH DASAR - Wendri Wiratsiwi (Universitas Muria Kudus, 2020)
This study aims to obtain information about the application of GLS or the School Literacy Movement in Cluster 01 Elementary School, Singgahan District, Tuban Regency. This study uses qualitative research with a case study research design. Data collection techniques used are observation, interviews and documentation. The results showed that, the application of the School Literacy Movement in the Cluster 01 Elementary School in Singgahan District was still at the habituation stage, namely 1) through reading aloud for about 15 minutes before learning for the low class and heart reading for the high class, 2) making a reading corner in each class, and 3) provide school library facilities. In implementing the School Literacy Movement there are still some obstacles including: 1) the lack of reading books; 2) lack of interest in reading students; 3) the teacher has not fully carried out this activity; 4) lack of guidance from the local education office about this School Literacy Movement; 5) and parents of students who are somewhat indifferent to the needs of children in order to support the School Literacy Movement. Whereas efforts to overcome obstacles during the implementation of the School Literacy Movement are: 1) seeking the fulfillment of reading books and library facilities by allocating funds for School Operational Costs (BOS); 2) SDN Saringembat I frees students to choose whenever students want to read, it does not have to be 15 minutes pre-learning so that a carpet is provided in the reading corner for them to use as a base for seating when they want to read; 3) SDN Saringembat I in order to improve the quality of GLS implementation by discussing and collaborating with other schools on the occasion when gathering at the Teacher Working Group activities in group 01 and the Principal Working Group (KKKS) or to other schools that are also GLS reference schools.